2019
DOI: 10.1016/j.ijmecsci.2019.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The height Digital Image Correlation (hDIC) technique for the identification of triaxial surface deformations

Abstract: This paper introduces the height digital image correlation (hDIC) technique for the identification of triaxial deformations. Conventional digital image correlation (DIC) uses pixel image intensity as the basis for the determination of in-plane displacement fields. We demonstrate the advantages of using the out-of-plane surface height and its variation during deformation to extract information about triaxial (in-plane and out-of-plane) displacement fields. Surface height maps can be obtained by optical profilom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…For this purpose, pixel intensities from height information are defined by a surface function, ( ′ , ′ ), using bi-cubic interpolation scheme which is formulated in Equation 3 that allows calculation of pixel intensity in the target subset at the coordinates defined by ( ′ , ′ ) where , is the coefficient of the pixel defined by the indices of and . Details of the hDIC process and formulation of the gradient descent method can be found in the study that introduces the hDIC technique [5] .…”
Section: The Hdic Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, pixel intensities from height information are defined by a surface function, ( ′ , ′ ), using bi-cubic interpolation scheme which is formulated in Equation 3 that allows calculation of pixel intensity in the target subset at the coordinates defined by ( ′ , ′ ) where , is the coefficient of the pixel defined by the indices of and . Details of the hDIC process and formulation of the gradient descent method can be found in the study that introduces the hDIC technique [5] .…”
Section: The Hdic Techniquementioning
confidence: 99%
“…The developed technique is widely used for analysing the deformations on 2D and 3D surfaces [3] that are difficult to investigate using classical experimental methods [4]. The height Digital Image Correlation (hDIC) technique was developed by Uzun and Korsunsky [5] for the determination of in-plane and out-of-plane deformations. Authors performed tensile test for in situ analysis of the method and showed that the proposed sub-pixel level correlation provides an accuracy of 99.89 % in terms of Pearson coefficient during the elastic deformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, 3D DIC techniques provide depth information with very low resolution and low precision over large areas [11][12][13][14]. The height digital image correlation (hDIC) [15] which is a true full field method and based on focus stacking 2 of 13 optical microscopy (FSOM), fills the gap between the two approaches. Beeck et al [16] also used confocal microscopy for obtaining topography information to perform DIC, but this scanning method is intrinsically slow [8] and requires complex finite element calculations and, accordingly, it is far from being a full field method.…”
Section: Introductionmentioning
confidence: 99%
“…The hDIC technique [15] was proposed recently for the correlation of optical profilometry data obtained using "infinite focus" microscopy. This allows the use of height data instead of the conventional grey scale colour intensity in typical digital images for the purpose of determination of triaxial surface displacements.…”
Section: Introductionmentioning
confidence: 99%